2013
DOI: 10.1016/j.immuni.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal High-Density Lipoprotein Induces Endothelial Dysfunction via Activation of Toll-like Receptor-2

Abstract: Endothelial injury and dysfunction (ED) represent a link between cardiovascular risk factors promoting hypertension and atherosclerosis, the leading cause of death in Western populations. High-density lipoprotein (HDL) is considered antiatherogenic and known to prevent ED. Using HDL from children and adults with chronic kidney dysfunction (HDL(CKD)), a population with high cardiovascular risk, we have demonstrated that HDL(CKD) in contrast to HDL(Healthy) promoted endothelial superoxide production, substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
214
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(227 citation statements)
references
References 65 publications
10
214
0
3
Order By: Relevance
“…Interestingly, Speer et al. reported that the level of SDMA, the structural isomer of ADMA, is elevated in high‐density lipoprotein (HDL) fraction of plasma from patients with chronic kidney dysfunction (CKD) 45. Notably, they also found that HDL from CKD patients or healthy HDL supplemented with SDMA not only loses the vasoprotective properties, but also changes toward a harmful lipoprotein that induces EC dysfunction, inflammation, and hypertension, suggesting that SDMA may also play an important role in pathogenesis of cardiovascular diseases under CKD condition 45.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Speer et al. reported that the level of SDMA, the structural isomer of ADMA, is elevated in high‐density lipoprotein (HDL) fraction of plasma from patients with chronic kidney dysfunction (CKD) 45. Notably, they also found that HDL from CKD patients or healthy HDL supplemented with SDMA not only loses the vasoprotective properties, but also changes toward a harmful lipoprotein that induces EC dysfunction, inflammation, and hypertension, suggesting that SDMA may also play an important role in pathogenesis of cardiovascular diseases under CKD condition 45.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the level of SDMA, the structural isomer of ADMA, is elevated in high‐density lipoprotein (HDL) fraction of plasma from patients with chronic kidney dysfunction (CKD) 45. Notably, they also found that HDL from CKD patients or healthy HDL supplemented with SDMA not only loses the vasoprotective properties, but also changes toward a harmful lipoprotein that induces EC dysfunction, inflammation, and hypertension, suggesting that SDMA may also play an important role in pathogenesis of cardiovascular diseases under CKD condition 45. However, our results showed that there was no significant difference in plasma SDMA between statins users and statins nonusers in 3 groups (whole population group: 0.48±0.30 vs 0.47±0.24; P =0.69; plasma ADMA level ≥0.49 μmol/L group: 0.48±0.24 vs 0.49±0.38; P =0.79; ADMA level <0.49 μmol/L group: 0.47±0.24 vs 0.47±0.21; P =0.91).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, SDMA has been found within HDL particles and linked to the functional impairment of HDL in these patients. 41 HDL from patients with CKD and HDL enriched with SDMA inhibited rather than increased endothelial nitric oxide production, endothelial cell migration, and endothelial repair as well as stimulated superoxide release by endothelial cells, and when injected in mice, raised arterial blood pressure. 41 The adverse effects of SDMA within HDL on endothelial cells are due to the interaction of SDMA with TLR2 on endothelial cells.…”
Section: Symmetric Dimethylargininementioning
confidence: 93%
“…For example, HDL of patients with CAD or chronic kidney disease (CKD) was found to inhibit rather than stimulate nitric oxide production because it gained the ability to interact with the lectin-like oxidized LDL receptor LOX-1 and the toll-like receptors TLR2 and TLR4, respectively. 40,41 Dysfunctional HDL in cardiovascular disease is not limited to CAD and acute coronary syndrome (ACS). Also in other cardiovascular diseases, such as heart failure, 42 ischaemic cardiomyopathy, 43 heart transplantion, 44,45 as well as in many conditions that are known to increase cardiovascular risk such as diabetes, CKD, acute and chronic inflammatory diseases, or familial hypercholesterolemia, [46][47][48] HDL has been found to lose its atheroprotective characteristics.…”
Section: Dysfunctional Hdl In Cardiovascular Diseasementioning
confidence: 99%
“…1). Beyond vascular homeostasis and vascular tone, it orchestrates diverse functions: smooth muscle cell proliferation [3,4], transendothelial leukocyte diapedesis [5,6], and thrombosis and thrombolysis [7].…”
Section: Introductionmentioning
confidence: 99%